Pengaruh Model PBL Melalui Pendekatan Pembelajaran Berdiferensiasi terhadap Pemahaman Siswa dalam Materi Keliling dan Luas Lingkaran - Agnes Verya Dianasari; Cholifahtur Rosidah; Rosmiati Rosmiati (Universitas 45 Surabaya, 2025)
This research aims to determine the effect of applying the Problem-Based Learning (PBL) model through a differentiated learning approach on students' understanding and learning outcomes in the topic of circumference and area of ​​circles in class VI-A. The method used in this research is a qualitative method with a descriptive approach, where data is collected through observation, interviews, documentation and LKPD. Student Worksheets (LKPD) are used to assess student learning outcomes quantitatively. The research results show that learning with a differentiated approach can improve students' understanding of the material being taught, because students are given the opportunity to choose a way of learning that suits their individual styles and needs. Apart from that, the application of the PBL model has also been proven to increase students' motivation, active participation and enthusiasm for learning. The results of the LKPD indicate a significant increase in student learning outcomes in the topic of circumference and area of ​​a circle. Differentiated learning with the PBL model has a positive impact, not only on learning outcomes, but also on student involvement in the learning process, creating an atmosphere that is more inclusive and relevant to the needs of each student. Thus, the PBL model with a differentiated approach can be an effective strategy in improving student learning outcomes in mathematics learning.